Aquaponic innovations: Optimizing carp growth in polyculture tank with plant diversity in Himachal Pradesh - SHARMA, MEENAKSHI; VERMA, TARUN; SHARMA, ARZOO (The Indian Journal of Animal Sciences, 2025)
Aquaponics integrates aquaculture and hydroponics, addressing the decreasing agricultural land in Himachal Pradesh. The rapid urbanization has led to an increased demand for nutritious food, especially protein-rich foods such as fish and fresh vegetables, as urban dewellers increasingly prioritize healthy eating habits. This 60-day experiment cultivated fingerlings of Hypophthalmichthys molitrix, Cyprinus carpio, Ctenopharyngodon idella, Cyprinus rubrofuscus, and Labeo dero alongside plants like Chenopodium album, Spinacia oleracea, Coriandrum sativum, Mentha spicata and Mentha piperita. Optimal water quality was maintained. Fish exhibited growth with an average length increase of 4.8±1.33 cm and weight gain of 16.05±3.76 g, achieving a feed conversion ratio (FCR) of 2.84±0.75. Plant growth averaged 30.15±0.91 cm, surpassing traditional methods. Hypophthalmichthys molitrix, Cyprinus carpio, Ctenopharyngodon idella, and Cyprinus rubrofuscus showed superior growth compared to Labeo dero. This study demonstrates aquaponic’s potential as a sustainable farming method, enhancing water efficiency and food security amidst land constrains.